IMPLEMENTASI SISTEM KEAMANAN JARINGAN MENGGUNAKAN METODE PACKET FILTERING BERBASIS ASA 5520 PADA PT. XYZ - Putra, Agung Triwicaksono; Setyowibowo, Sigit; Arifin, Samsul (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2019)
PT. XYZ is one of the fourth largest cigarette producers in Indonesia with a market share of 7%. Has more than 40 marketing offices spread throughout Indonesia. Every branch offices have sales that using public internet to upload and download data from headquarter server’s. Constraints faced by PT. XYZ that public server used for upload and download process was down due to attacker from external network, causing disruption to sales team activities. Sales team can’t achieve the target to visit 6427 outlets from total 64980 outlets. The purpose of this research is to develop a network security system environment that able to protect internal servers of PT. XYZ from the threat both internal network and extenal. This study implemented using packet filtering method that applied to CISCO ASA 5520 device. The network security system that already implemented are able to protect the server from unauthorized security threats so it does not interfere sales team's operations. Keywords: Network Security, Packet Filtering, ASA 5520